Prevalence of Myopia and Its Associated Factors Among Japanese Preschool Children - Matsumura, Saiko; Dannoue, Kazuhiko; Kawakami, Momoko; Uemura, Keiko; Kameyama, Asuka; Takei, Anna; Hori, Yuichi (Frontiers in Public Health, 2022)
Purpose To investigate the prevalence of myopia and factors associated with spherical equivalent (SE), axial length (AL), and axial length to corneal radius of curvature (AL/CR) ratio among Japanese preschool children. Study Design Prospective observational study. Methods This cross-sectional study evaluated subjects aged 4–6 years from a preschool. Non-cycloplegic autorefraction was measured using the Spot Vision Screener, while AL and corneal radius (CR) were measured using the Myopia Master. Parental myopia and environmental factors were investigated using the myopia-related factor questionnaire. The worse eye with higher myopic SE was chosen for analysis, and multiple linear regression models was performed using AL, SE, and AL/CR ratio as dependent variables. Results A total of 457 out of 514 participants (239 males, 52.3%) aged 4–6 years (mean 4.77 ± 0.65 years) were included. The mean SE was 0.13 ± 0.63 D, AL was 22.35 ± 0.67 mm, CR was 7.76 ± 0.25 mm, and AL/CR ratio was 2.88 ± 0.72. The overall prevalence of myopia and high myopia were 2.9 and 0.2%, respectively. Multiple regression analysis showed that myopic SE was significantly associated with male sex (β = −0.14, p = 0.02) and parental myopia (β = −0.15, p = 0.04). Meanwhile, longer AL was significantly associated with older age (β = 0.13, p = 0.02), male sex (β = 0.44, p < 0.001), parental myopia (β = 0.24, p = 0.01), and screen time (including smartphones, tablets, and computers) (>1 h, β = 0.14, p = 0.04). A higher AL/CR was significantly associated with older age (β = 0.02, p < 0.001), male sex (β = 0.03, p < 0.001), ratio and parental myopia (β = 0.03, p = 0.02). Conclusion The prevalence of myopia and high myopia were 2.9 and 0.2%, respectively, among Japanese preschool children in 2021. Longer AL was associated with older age, male sex, parental myopia, and screen time in children aged 4–6 years. Children with a high risk of myopia can be identified early based on parental myopia information for early prevention.